Desing of 3D printed veterinary capsule devices for supplement administration - Gallo, Loreana Carolina (2021)
Urea is commonly employed in ruminant feed supplementation, however is rapidly hydrolyzed in the rumen. Therefore, modifying the urea release has become a pharmacotechnical challenge. In this work, a proof of concept study was developed to test the feasibility of using Fused Deposition Modeling-3D printing (3DP) to create veterinary capsule devices (CDs) that could allow the control of urea release. Three designs were assayed: D1 = one-compartment capsule with body and cover printed in polylactic acid (PLA), D2 = one-compartment capsule with body of PLA and cover of polyvinyl alcohol (PVA) and D3 = multi-compartment capsule with cover and body of PLA, the body presenting a PVA orifice in one extreme and five PVA partitions inside. The release of urea from the CDs was performed in 1 liter of distilled water, 40 ºC and 50 rpm. Two sinkers of differents weights and two types of paddles were evaluated. D1 showed no release of urea within 24 hours. D2 exhibited a retard release without influence of sinkers and paddles. D3 showed immediate and prolonged profiles, thus the release was affected by sinkers/paddles and some printing errors. These preliminary designs showed the possibility of using 3DP as a technological platform to modify the urea release in ruminant feed supplementation.